THE INFLUENCE OF REFERRAL SERVICE ON HOUSEHOLD ACCESS TO HEALTHCARE SERVICES IN ELDORET MUNICIPALITY, KENYA - Ajwang, Nicholas Walter Otieno (European Scientific Journal, ESJ, 2013)
The severe shortage and unfavourable distribution of health services continues to widen with observed disparities and imbalance in funding and poor distribution of human resources that continues to be limited since those in medical training have also been increasing slowly. The main objective of the study was to establish the influence of referral service on household access to healthcare services in Eldoret Municipality, Kenya. The specific objectives of the study were: to examine the influence of referral service on household access to a healthcare provider; and to examine the influence of referral services on household access to healthcare services. Results of the study will widen understanding on the referral system and access to healthcare. Survey research design was employed for the study. The unit of analysis constituted household heads in Eldoret. Stratified, systematic, purposive and convenience sampling procedures were used to arrive at a sample of 260 household heads whom were systematically interviewed concerning matters relating to access to referral care services. An interview schedule prepared especially for the study was administered to the selected household heads. Attention was paid to the factors which predispose the decision to access or not to access the available referral care services. Data was analysed using Statistical Package for Social Sciences (SPSS). On the basis of this study, a number of considerations are derived for the planning of healthcare in the country. Also a number of recommendations are given for future studies that will improve access to healthcare.